On some F - contraction of Piri–Kumam–Dung–type mappings in metric spaces - Vujaković, Jelena; Radenović, Stojan (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: This paper establishes some new results of Piri-Kumam-Dung-type mappings in a complete metric space.Тhe goal was to improve the already published results.Methods: Using the property of a strictly increasing function as well as the known Lemma formulated in (Radenović et al, 2017), the authors have proved that a Picard sequence is a Cauchy sequence.Results: New  results were obtained concerning the F - contraction mappings of  in a complete metric space. To prove it, the authors used only property (W1).Conclusion: The authors believe that the obtained results represent a significant improvement of many known results in the existing literature.
Keywords: Banach principle; F-contractive mapping; metric space; fixed point.